2017
DOI: 10.1093/ee/nvx181
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Huge Immigration of Sogatella furcifera (Hemiptera: Delphacidae) to Southern China in the Spring of 2012

Abstract: Sogatella furcifera (Horváth) is a migratory rice pest that periodically erupts across Asia, and early immigration is an important cause of its outbreak. The early immigration of S. furcifera into southern China shows evident annual fluctuations. In the spring of 2012, the huge size of the immigrant population and the large number of immigration peaks were at levels rarely seen prior to that year. However, little research has been done on the entire process of round-trip migration to clarify the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This pattern has also been identified in a recent analysis based on genome-wide SNPs ( Chen et al, 2021 ), where populations of Yunnan are the source in two consecutive years. While the populations from ICP were not sampled in Chen et al (2021) ’s study, previous analysis of many insect pests have found this region to be the source of insect immigration in China based on trajectory modeling [e.g., Nilaparvata lugens (Stål) ( Hu et al, 2014 ); Sogatella furcifera ( Sun et al, 2017 ); Spodoptera frugiperda ( Li et al, 2020 )] and genetic analysis [e.g., Nilaparvata lugens (Stål) ( Hu et al, 2019 )]. The year-round suitable temperature in Yunnan and Indo-China Peninsula (e.g., northern and central Vietnam, Laos, and northeastern Thailand) may be the reason for maintaining a large number of populations ready for migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern has also been identified in a recent analysis based on genome-wide SNPs ( Chen et al, 2021 ), where populations of Yunnan are the source in two consecutive years. While the populations from ICP were not sampled in Chen et al (2021) ’s study, previous analysis of many insect pests have found this region to be the source of insect immigration in China based on trajectory modeling [e.g., Nilaparvata lugens (Stål) ( Hu et al, 2014 ); Sogatella furcifera ( Sun et al, 2017 ); Spodoptera frugiperda ( Li et al, 2020 )] and genetic analysis [e.g., Nilaparvata lugens (Stål) ( Hu et al, 2019 )]. The year-round suitable temperature in Yunnan and Indo-China Peninsula (e.g., northern and central Vietnam, Laos, and northeastern Thailand) may be the reason for maintaining a large number of populations ready for migration.…”
Section: Discussionmentioning
confidence: 99%
“…The year-round suitable temperature in Yunnan and Indo-China Peninsula (e.g., northern and central Vietnam, Laos, and northeastern Thailand) may be the reason for maintaining a large number of populations ready for migration. We thus suggest that these regions should not only be important for effective control of rice pests ( Hu et al, 2014 ; Sun et al, 2017 ), but also for the management of other important vegetable pests, such as P. xylostella . We additionally found several regions such as Fujian and Guangdong were always being the receivers in these regions, a pattern that was consistent over 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, we found that the main migration sources of the WBPH in Yunnan Province, China include Myanmar, Vietnam, Laos, and Cambodia [13,[20][21][22]. However, it is important to note that our previous studies in Myanmar primarily focused on samples from the southern region of the country.…”
Section: Introductionmentioning
confidence: 92%
“…The WBPH that migrated to China continue to move toward northern China on prevailing winds [4,5]. Based on trajectory analysis, the rice paddy elds in the Greater Mekong Subregion (GMS), including Laos, Thailand, Vietnam, and parts of Yunnan Province in China, are considered to be important overwintering sites [6,7]. Molecular marker data have con rmed that the extensive gene ow of WBPH occurs between Yunnan Province and neighboring countries in the GMS [8,9].…”
Section: Introductionmentioning
confidence: 99%